Aircraft batteries: current trend towards more electric aircraft. Issue 2 (1st June 2017) - Tariq, Mohd; Maswood, Ali I.; Gajanayake, Chandana Jayampathi; Gupta, Amit Kumar
Abstract : Competition in the aircraft industry market and global warming has driven the industry to think along economic and environmental lines. This has resulted in the emergence of more electric aircraft (MEA). The increase in the power demand of aircraft, especially in the last two decades, coupled with advancement in battery materials and technology has led to the development of many high energy density batteries. This study presents an overview of the battery systems for MEA. In this paper, a study on the battery technologies used in aircraft in the last five decades is being done. A general background of the battery system is presented and the performance of the batteries based on energy densities and low temperature capabilities are evaluated and discussed. Evolution of MEA with its power system architecture and load profile is presented to understand the requirements of the battery system. Weight saving and cost analysis is done for the Li‐ion and Ni–Cd batteries with respect to the requirement of an MEA 'Aircraft X'. Battery management system (BMS) for Li‐ion batteries is also explored and discussed. Based on the analysis, Li‐ion battery is selected and integrated with the power distribution DC network for future MEA.